Numerical hydrodynamic modelling of a pitching wave energy converter - Bhinder, Majid A.; Rahmati, M.T.; Mingham, C.G.; Aggidis, G.A. (European Journal of Computational Mechanics, 2015)
Two computational methodologies – computational fluid dynamics (CFD) and the numerical modelling using linear potential theory based boundary element method (BEM) are compared against experimental measurements of the motion response of a pitching wave energy converter. CFD is considered as relatively rigorous approach offering nonlinear incorporation of viscous and vortex phenomenon and capturing of the flow turbulence to some extent, whereas numerical approach of the BEM relies upon the linear frequency domain hydrodynamic calculations that can be further used for the time-domain analysis offering robust preliminary design analysis. This paper reports results from both approaches and concludes upon the comparison of numerical and experimental findings.